Effects of transcranial direct current stimulation on non-motor functions in individuals with Parkinson’s disease: a systematic review and meta-analysis - Li, Qiyu; Ye, Hanmei; Ye, Cheng; Huang, Mi (Frontiers in Neuroscience, 2025)
BackgroundParkinson’s disease (PD) is a highly prevalent neurodegenerative disorder that poses a significant mental and physical burden on patients, markedly diminishing their quality of life. This study aimed to systematically evaluate the effects of transcranial direct current stimulation (tDCS) on cognitive functions, mood state, sleep function, and overal quality of life in individuals with PD.MethodsRelevant literature was sourced from multiple databases, ultimately including 22 studies with a total of 1324 individuals. Data analysis was conducted using meta-analysis software. The protocol was registered in PROSPERO (CRD42024599943).ResultsThe findings indicated that tDCS significantly enhanced cognitive function, alleviated anxiety and depression, increased sleep duration, improved sleep efficiency, reduced arousal index, and ameliorated daytime sleepiness, while also enhancing activities of daily living. However, discrepancies were noted across various assessment scales, including the Mini-Mental State Examination, the Parkinson’s Disease Cognitive Rating Scale, delayed recall metrics, sleep scales, and Parkinson’s Disease Questionnaire. Additionally, individuals with PD displayed good tolerance to tDCS.ConclusionOverall, tDCS shows promise in improving non-motor symptoms and enhancing quality of life for individuals with PD. Nonetheless, large-scale trials are necessary to confirm these results further.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024599943, Identifier: CRD42024599943.